Genome-Wide Identification of QTL for Seed Yield and Yield-Related Traits and Construction of a High-Density Consensus Map for QTL Comparison in Brassica napus - Zhao, Weiguo; Wang, Xiaodong; Wang, Hao; Tian, Jianhua; Li, Baojun; Chen, Li; Chao, Hongbo; Long, Yan; Xiang, Jun; Gan, Jianping; Liang, Wusheng; Li, Maoteng (Frontiers in Plant Science, 2016)
Seed yield (SY) is the most important trait in rapeseed, which was determined by multiple seed yield-related traits (SYRTs) and also easily subject to environmental influence. Lots of quantitative trait loci (QTL) for SY and SYRTs were reported in Brassica napus. However, no studies have focused on SY and seven agronomic traits affecting SY simultaneous. Genome-wide QTL analysis for SY and seven SYRTs in eight environments was conducted in a doubled haploid population containing 348 lines. Totally, 18 and 208 QTLs for SY and SYRTs were observed, respectively, and then these QTLs were integrated into 144 consensus QTLs by a meta-analysis. Three major QTLs for SY were observed, including cqSY-C6-2 and cqSY-C6-3 that expressed stably in winter cultivation area for three years and cqSY-A2-2 only expressed in spring rapeseed area. Trait-by-trait meta-analysis revealed that the 144 consensus QTLs were integrated into 72 pleiotropic unique QTLs. Among them, all the unique QTLs affected SY, except for uq-A6-1, including uq.A2-3, uq.C1-2, uq.C1-3, uq.C6-1, uq.C6-5 and uq.C6-6 could also affect more than two SYRTs. According to high density consensus map construction and QTL comparison from literature, 36 QTLs from five populations were co-localized with QTLs identified in this study. In addition, 13 orthologs genes were observed, including five each genes for SY and SW, one each gene for BY, BH and PH, respectively. The genomic information of these QTLs would be valuable in hybrid cultivar breeding, and be helpful to analyze QTL expression in different environments.